Early Career Physical Therapist Faculty Connecting With Others for Scholarly Activity: A Grounded Theory Study. Issue 1 (27th March 2021) - Becker, Betsy J.; Shope, Ron; Willett, Gilbert; Von Essen, Susanna; Kennel, Victoria
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The professional relationships of early career physical therapist (PT) faculty aid in career advancement by supporting scholarly activity. A recent study suggested that a professional network structure that is less interconnected is an effective network for more scholarly activity. However, no studies have addressed the process of how early career PT faculty build their network. The purpose of this study is to develop a theoretical model that explains the process that early career PT faculty use to develop effective networks for scholarly activity. Methods: Participants were purposely selected to represent variations in scholarly productivity and effectiveness in their professional network. One-on-one interviews were conducted with 20 early career PT faculty, representing 15 institutions from 12 states. Questions focused on why individuals were included in the network, how they were connected, and examples of the outcomes of the relationships. Conceptual depth for the theory development was determined through conceptual maps, coding trees, axial coding, member checking, and peer debriefing. Results: We present a theoretical model of the process early career PT faculty members use to develop effective networks for scholarly activity. Motivations to develop network connections were meeting accreditation standards, job requirements, and a desire to contribute to the knowledge base. Network development strategies included reaching out to previously established connections, making new acquaintances within one's current institution, unplanned "fluke" encounters, and "cold calling." Outcomes of developing network connections were new opportunities, advancing connections, and receiving feedback. Challenges to this process were a lack of time, funding, individual elements, and institutional factors. Discussion and Conclusion: This theory improves our understanding of the process early career faculty use to build professional network connections and use the relationships to generate a scholarly agenda. Traditional introductions, self-initiated contact, and taking advantage of chance encounters can all help early career faculty advance their network connections. Implementing these strategies to develop connections is not only the responsibility of the individual faculty member but also must be encouraged by professional associations and educational institutions. This study underscores the importance of early career faculty connecting with others to be successful in higher education.